Pembelajaran Gerak Dasar Tari Kijang Pada Anak Usia Dini di Sanggar Rangga Setra Manik Pakuan Tasikmalaya - Seni Lidusyiami; Asti Tri Lestari; Budi Dharma (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The research is entitled "Learning the Basic Movements of the Kijang Dance in Early Childhood at Sanggar Rangga Setra Manik Pakuan, Tasikmalaya City". The aim is to find out the process of learning deer dance and the results of learning carried out at Sanggar Rangga Setra Manik Pakuan. This research focuses on how the learning process and learning outcomes are used or applied in learning the basic movements of deer dance at Sanggar Rangga Setra Manik Pakuan, Tasikmalaya city. This research uses qualitative research methods that are descriptive analysis. This research was carried out through field studies in the form of observations, interviews and documentation, which then became a source of data for analysis. The results of the findings carried out by the researchers were that the process of learning deer dance at Sanggar Rangga Setra Manik Pakuan carried out training for 2 months or 8 meetings, and during learning used the drill/rehearsal method. At the end of the learning outcomes, children take exams as a form of class promotion, which are carried out in various public places, with the aim of training the child's level of self-confidence.